Comparing ARIA‐E severity scales and effects of treatment management thresholds. Issue 1 (2nd December 2022) - Klein, Gregory; Scelsi, Marzia A.; Barakos, Jerome; Fiebach, Jochen B.; Bracoud, Luc; Suhy, Joyce; Delmar, Paul; Lyons, Marco; Wojtowicz, Jakub; Bullain, Szofia; Barkhof, Frederik; Purcell, Derk
Abstract: Introduction: Amyloid‐related imaging abnormalities–edema (ARIA‐E) is associated with anti‐amyloid beta monoclonal antibody treatment. ARIA‐E severity may be assessed using the Barkhof Grand Total Scale (BGTS) or the 3‐ or 5‐point Severity Scales of ARIA‐E (SSAE‐3/SSAE‐5). We assessed inter‐ and intra‐reader correlations between SSAE‐3/5 and BGTS. Methods: Magnetic resonance imaging scans were collected from 75 participants in the SCarlet RoAD and Marguerite RoAD studies. Three neuroradiologists reviewed scans at baseline and at follow‐up. Concordance in dichotomized ARIA‐E ratings was assessed for a range of BGTS thresholds. Results: SSAE‐3/5 scores correlated with BGTS scores, with high inter‐reader intraclass correlation coefficients across all scales. There was high agreement in dichotomized ratings for SSAE‐3 > 1 versus BGTS > 3 for all readers (accuracy 0.85–0.93) and between pairs of readers. Discussion: SSAE‐3/5 showed high degrees of correlation with BGTS, potentially allowing seamless transition from the BGTS to SSAE‐3/5 for ARIA‐E management.